2009
DOI: 10.1111/j.1541-0420.2008.01103.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Random‐Effect Model Misspecification in Generalized Linear Mixed Models for Binary Response

Abstract: Generalized linear mixed models (GLMMs) are widely used in the analysis of clustered data. However, the validity of likelihood-based inference in such analyses can be greatly affected by the assumed model for the random effects. We propose a diagnostic method for random-effect model misspecification in GLMMs for clustered binary response. We provide a theoretical justification of the proposed method and investigate its finite sample performance via simulation. The proposed method is applied to data from a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 15 publications
0
31
0
7
Order By: Relevance
“…In this case, the CPI model yields nearly the same fitted values as the MEM model, so we consider only the MEM model from this point. A variety of methods have been proposed to assess the assumption of independent normally distributed random effects . We use several of these methods to assess the assumption in this case; details are in Appendix S3.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the CPI model yields nearly the same fitted values as the MEM model, so we consider only the MEM model from this point. A variety of methods have been proposed to assess the assumption of independent normally distributed random effects . We use several of these methods to assess the assumption in this case; details are in Appendix S3.…”
Section: Resultsmentioning
confidence: 99%
“…If the mixed effects model used to estimate conditional effects is misspecified, the estimates are difficult to interpret and, even if regression diagnostics can help, 29 standard errors (SEs) are not robust. Fortunately, Murray et al 30 and Fu 31 have shown that mixed models are robust to substantial violation of the normality assumptions for member- and group-level errors, so long as balance is maintained at the group level.…”
Section: Developments In the Analysis Of Parallel Group-randomized Trmentioning
confidence: 99%
“…However, this class of models makes a strong assumption about the distribution of random effects. For computational convenience, random effects are assumed to be normal, but this assumption may be unrealistic for some applications [1]. Since the random effects are not observable, checking the assumption is difficult, and if the true distribution of the random effects is far from normality, the estimation and inferences could be considerably affected.…”
Section: Introductionmentioning
confidence: 99%